Entrenamiento de resistencia para el desarrollo de la capacidad aeróbica del futbolista para competir en la altura - Cerruffo Bermeo, Luis Antonio (2025)
Endurance is defined as the body's ability to sustain prolonged physical effort, which involves both aerobic and anaerobic components. In soccer, endurance plays a fundamental role since the demands to which players are subjected are very high. The present investigation worked with a descriptive methodology and a quantitative approach, for the realization of the same we had a sample of 20 players of the Club Deportivo Santa Rita de Vinces, category U17, to which the Cooper test was applied to assess the aerobic endurance that soccer players have to compete at altitude, in addition to 4 members of the coaching staff, which was applied a survey to determine the level of knowledge they had about the training of aerobic endurance to compete at altitude. After performing the proper analysis and interpretation of data, it was obtained as a result that both players and coaching staff consider important endurance training to develop the aerobic capacity in soccer players. Considering the evidence obtained through the physical tests performed on the club's players, it became evident that there is a deficiency of endurance in the club's players, for this problem a methodological proposal for endurance training for the development of aerobic capacity to compete at high altitude was proposed for the players of the Santa Rita Sports Club, category U-17 of Vinces canton.